Fantasy in Death - Book 30 - Robb, J. D., 1950- (New York : G.P. Putnams Sons, 2010)
NYPSD Lieutenant Eve Dallas is having as much trouble figuring out how Bart Minnock, founder of the computer- gaming giant U-Play, was murdered as who did the murdering in this mystery revolving around a fantasy game of ultimate seduction and death.
Keywords: Dallas, Eve (Fictitious character) -- Fiction; Policewomen -- Fiction; Women detectives -- Fiction; Virtual reality -- Fiction; Electronic games industry -- Fiction; New York (N.Y.) -- Fiction; Detective and mystery fiction